2021
DOI: 10.33448/rsd-v10i1.11637
|View full text |Cite
|
Sign up to set email alerts
|

Review- The periodontal pathogen Treponema denticola: an atherosclerosis risk factor

Abstract: Objective: Treponema denticola “T. denticola” is a pathogen associated with periodontal diseases that exhibits capacity for adherence, invasion, and colonization of host tissues, which allows alternating its location and damage in different sites of human body. This review aimed to discuss different studies that detected T. denticola in atherosclerotic plaques, demonstrating the importance of periodontal disease on the systemic health and the necessity of exploring the outcome of this colonization apart from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(89 reference statements)
1
2
0
Order By: Relevance
“…To illustrate a few microbial flow paths, we detected Treponema denticola, an oral bacterium commonly associated with periodontal disease, in the heart. This observation is in line with studies that have linked Treponema denticola to atherosclerosis through its invasion of aortic tissue [34][35][36] (SI Figure 5). Streptococcus pyogenes, another oral bacterium whose infection can lead to rheumatic heart disease 37 , was also detected in the heart (SI Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…To illustrate a few microbial flow paths, we detected Treponema denticola, an oral bacterium commonly associated with periodontal disease, in the heart. This observation is in line with studies that have linked Treponema denticola to atherosclerosis through its invasion of aortic tissue [34][35][36] (SI Figure 5). Streptococcus pyogenes, another oral bacterium whose infection can lead to rheumatic heart disease 37 , was also detected in the heart (SI Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…T. denticola , being one of the most resistant bacteria frequently identified in primary dentition infection, is highly associated with periodontal diseases. It is commonly isolated from periodontal pockets of adults and it has great influence on the inflammation by stimulating the production of cytokines and it also causes disruption of tissue homeostasis [ 41 ]. Based on that, T. denticola is predominantly linked with severe periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified significant strain variation in the biofilm formation capabilities of T. denticola . This could be partially dependent on the bacterium’s mobility, which was shown to differ greatly between strains [ 73 ].…”
Section: Periodontal Pathogens Virulence Factors and Host Responsementioning
confidence: 99%